Axion-like particles from primordial black holes shining through the Universe. Issue 8 (30th August 2021) - Schiavone, Francesco; Montanino, Daniele; Mirizzi, Alessandro; Capozzi, Francesco
Abstract: We consider a cosmological scenario in which the very early Universe experienced a transient epoch of matter domination due to the formation of a large population of primordial black holes (PBHs) with masses M ≲ 10 9 g, that evaporate before Big Bang nucleosynthesis. In this context, Hawking radiation would be a non-thermal mechanism to produce a cosmic background of axion-like particles (ALPs). We assume the minimal scenario in which these ALPs couple only with photons. In the case of ultralight ALPs ( m a ≲ 10 -9 eV) the cosmic magnetic fields might trigger ALP-photon conversions, while for masses m a ≳ 10 eV spontaneous ALP decay in photon pairs would be effective. We investigate the impact of these mechanisms on the cosmic X-ray background, on the excess in X-ray luminosity in Galaxy Clusters, and on the process of cosmic reionization.